Radiation pattern reconfigurable fm antenna - Gopalakrishnan, Jaya Bharath; Sabapathy, Thennarasan; Jusoh, Muzammil; Al-Bawri, Samir; Yaasin, M.N.; Osman, Mohamed Nasrun; Abd Rahim, Hasliza; Mat, Mohd Hafizudin; A. Majid, Huda; Ali, Tarmizi; Abdul Wahab, Yasmin (2019)
In this work, a radiation pattern reconfigurable antenna design using compact printed spiral monopoles that operates at 102 MHz is reported. The proposed antenna changes its radiation behaviour that responds towards a desired direction with the use of RF switches. The antenna is printed on a 76.6mm × 50mm PCB layer providing more than 20MHz bandwidth at -10 dB threshold and is easily fabricated with low manufacturing cost. The antenna was also simulated on 500mm × 500mm ground plane that represents the roof top of a vehicle